MGAlignIt: a web service for the alignment of mRNA/EST and genomic sequences - Lee, Bernett T. K. (Oxford University Press, 2003)
Splicing is a biological phenomenon that removes the non-coding sequence from the transcripts to produce a mature transcript suitable for translation. To study this phenomenon, information on the intron–exon arrangement of a gene is essential, usually obtained by aligning mRNA/EST sequences to their cognate genomic sequences. MGAlign is a novel, rapid, memory efficient and practical method for aligning mRNA/EST and genome sequences. We present here a freely available web service, MGAlignIt (http://origin.bic.nus.edu.sg/mgalign/mgalignit), based on MGAlign. Besides the alignment itself, this web service allows users to effectively visualize the alignment in a graphical manner and to perform limited analysis on the alignment output. The server also permits the alignment to be saved in several forms, both graphical and text, suitable for further processing and analysis by other programs.